2005
DOI: 10.1095/biolreprod.104.036145
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Basigin, an Inducer of Matrix Metalloproteinases, in the Rat Ovary1

Abstract: The extensive tissue remodeling that occurs during follicular development, ovulatory rupture, and the formation and regression of the corpus luteum (CL) requires local degradation of the extracellular environment by matrix metalloproteinases (MMPs). This report characterizes the expression pattern of basigin (Bsg), a putative regulator of MMP induction, in the rat ovary. An induced superovulation model (eCG/hCG) was used in immature rats to evaluate Bsg expression profiles in ovaries collected during the folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…In contrast, basigin mRNA and protein were detectable in both new corpus lutea and corpus lutea from previous cycles in the rat ovary (Smedts and Curry, 2005), suggesting that basigin expression in corpus lutea is species-specific. Still, the ovaries of Bsg-null mutant mice exhibit normal folliculogenesis and corpus lutea (Kuno et al, 1998), as well as normal progesterone levels on day 8 of pseudopregancy (Chen et al unpublished data).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, basigin mRNA and protein were detectable in both new corpus lutea and corpus lutea from previous cycles in the rat ovary (Smedts and Curry, 2005), suggesting that basigin expression in corpus lutea is species-specific. Still, the ovaries of Bsg-null mutant mice exhibit normal folliculogenesis and corpus lutea (Kuno et al, 1998), as well as normal progesterone levels on day 8 of pseudopregancy (Chen et al unpublished data).…”
Section: Discussionmentioning
confidence: 84%
“…EMMPRIN is associated with cell growth and adhesion [25], angiogenesis [26,27], chaperone functions [28,29], immune cell activation [30], proMMP-1 activation [31], MMP induction [32,33], and ECM degradation and remodeling [34]. EMMPRIN is highly associated with the menstrual cycle [35,36], estrous cycle, and pregnancy in mice [17] and rats [37], as well as ovulation and luteogenesis [38]. In cow, EMMPRIN may be involved in endometrial remodeling for implantation same as those in other species because recent reports showed that MMP and ECM-related molecules including EMMPRIN expressed in bovine endometrium and placenta [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Young 1‐month‐old female rats were treated hormonally to simulate pregnancy conditions. The hormonal treatment consisted of successive injections of 25 international units (IU) of human follicle‐stimulating hormone and 48 hr later 25 IU of human chorionic gonadotropin (hCG) (McDonnel Smedts & Curry, ). The day following administration of hCG was considered Day 1 of pseudopregnancy, and oviducts ( n = 4) were collected 72 hr posttreatment (SP3).…”
Section: Methodsmentioning
confidence: 99%